2001
DOI: 10.2136/sssaj2001.6551392x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Nonionic Surfactant on the Water Retention Properties of Unsaturated Soils

Abstract: Surfactants are widely used in household products, industrial pro-100 g L Ϫ1) of the formulated herbicide product and 0.1 cesses and as adjuvants to improve the delivery and effectiveness of to 0.5% (1 to 5 g L Ϫ1) of the spray tank solution. As a agrochemicals. Due to their amphiphilic nature, surfactants tend to accumulate at gas-liquid and solid-liquid interfaces, and thus, have result, the amount of surfactant applied to agricultural the potential to influence water flow and retention in unsaturated lands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 32 publications
3
59
0
1
Order By: Relevance
“…Results demonstrate that for significantly high surface coverage of impurities, the (gas-side) contact angle can significantly reduce and indeed exhibit a value close to that suggested by experimental findings [7,19]. Such lowering of the contact angle is similar to that which are suggested by experimental evidences of equilibrium adsorption of common surfactants to water [36,37]. The…”
Section: Discussionsupporting
confidence: 80%
“…Results demonstrate that for significantly high surface coverage of impurities, the (gas-side) contact angle can significantly reduce and indeed exhibit a value close to that suggested by experimental findings [7,19]. Such lowering of the contact angle is similar to that which are suggested by experimental evidences of equilibrium adsorption of common surfactants to water [36,37]. The…”
Section: Discussionsupporting
confidence: 80%
“…Although the structure and function of the molecules of the wide number of surfactants vary widely, all possess a hydrophilic "head" group and a hydrophobic "tail" group (Karagunduz, 2001). Their head bonds strongly with water, while their tail adsorbs to surfaces such as clay minerals, air molecules in pores, or hydrophobic organic substances in soil (Kuhnt, 1993;Tumeo et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Their head bonds strongly with water, while their tail adsorbs to surfaces such as clay minerals, air molecules in pores, or hydrophobic organic substances in soil (Kuhnt, 1993;Tumeo et al, 1997). The net effect is an apparent lowering of the interfacial tension between air-water and soil-water surfaces (Rosen, 1989;Karagunduz, 2001). This is especially noticeable when the soil particles have hydrophobic, or water repellent, coatings (Doerr et al, 2007;Kostka et al, 2007;Hallett, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this relationship, matric suction in any unsaturated soil system wetted with surfactant is scaled by the ratio of the surface tension of the solution to the surface tension of the water (or any reference liquid). Karagunduz et al (2001) reported that in addition to surface tension, the presence of surfactant might also alter the contact angle of the liquid-gas interface.…”
Section: ψ 2 Cos (2-36)mentioning
confidence: 99%